EDITORIAL CONDITIONS OF DEVELOPMENT OF INFORMATION CULTURE OF STUDENTS OF 10-11 GRADE IN THE PROCESS OF INNOVATIVE EDUCATION - Kоmilоvа Zirоаtхоn (International Scientific and Current Research Conferences, 2023)
The article expresses the peculiarities of teachers’ pedagogical communication abilities formation.